Clinical and microbiological evaluation of stabilised periodontal patients undergoing early stage of orthodontic treatment - Asma Alhusna Abang Abdullah,; Juhaida S,; Badiah Baharin,; Zaleha Shafiei,; Rohaya Megat Abdul Wahab, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Orthodontic treatment may affect the equilibrium of oral microbiota which plays a major role in aetiology of periodontal disease. This prospective clinical study aimed to assess the periodontal health and microbiological profile of healthy (Group 1) and stabilised periodontal (Group 2) patients throughout three months of orthodontic treatment. Upper and lower fixed orthodontic appliances were bonded. Periodontal health was assessed using plaque score (PS), bleeding on probing (BOP) and pocket depth (PD). 29 sites were taken for subgingival plaque sampling. Plaque samples were inoculated on Trypticase Soy Blood Agar (TSBA) and Trypticase Soy Bacitracin Vancomycin (TSBV) agar for assessment of aerobe, anaerobe, black pigmented bacteria (BPB) and Aggregatibacter actinomycetemcomitans. All the measurements were taken before bonding (T0), 1 week (T1), 1 month (T2) and 3 months post-bonding (T3). Generally, periodontal health in both groups were almost similar. After 1 week, the number of aerobes was significantly higher in Group 1 (88%) while the anaerobes were significantly higher in Group 2 (45%). A. actinomycetemcomitans was higher in Group 1 at T0 and T1 but was significantly higher in Group 2 at T3. BPB was minimal at all time with no significant difference. Thus, during the first 3-month of orthodontic treatment, there were significant changes in the number of aerobes-anaerobes in both healthy and stabilised periodontal patients. Pathogenic bacteria would increase during early treatment of orthodontics.